MODAL SOSIAL PEDAGANG NANAS DI DESA RIMBAPANJANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Azzah, Siti Fathin; Marnelly, T. Romi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Traders are people who carry out trade, trade goods, both those that are not self-produced and those that are self-produced to make a profit. Commercial acts in general are acts of buying goods for resale. Traders usually sell around the market, but there are also those who sell outside the market by gathering and selling the same type of goods so as to form certain groups of goods traders. individual attachment to social relations is a reflection of oneself as a social being. Social networks are formed because of mutual trust, knowing each other, informing each other, and reminding each other of something. As Putnam said, thoughts and theories about social capital are indeed based on the fact that "networks between people" are the most important part of a community. In their daily lives, pineapple traders along the Long Jungle Road do not only sell pineapples to the public. The duration of experience in selling pineapples makes old traders have a lot of networks in terms of supplying merchandise so that they become traders. Keyword : Pineapple seller, Social Network, Trust